(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To objectively determine longitudinal changes in corneal optical density (COD) in patients with bacterial keratitis (BK). Methods: Thirty patients with unilateral BK (mean age ± standard deviation [SD], 44.7 ± 11.5 years) underwent examination. Fellow eyes were used as controls. Optical densitometry was performed using the corneal topography system Pentacam AXL at admission and days 7 and 14 of treatment. Results: At presentation and days 7 and 14 of treatment, the average median (interquartile range [IQR]) COD value for the affected eyes was 92.8 (55.6-99.6), 89.7 (51.1-97.3) and 80.6 (32.0-93.1) grayscale units (GSU), respectively (p < 0.05), indicating a decrease in inflammatory infiltration, and the average mean (SD) COD value for the control eyes was 19.6 ± 3.0, 19.9 ± 2.8, and 19.7 ± 2.6 GSU, respectively, with no statistically significant difference. Conclusion: The use of optical densitometry for monitoring corneal transparency in eyes treated for BK over a two-week period enabled objective recording of a gradual reduction in median (IQR) COD values in the affected eyes from 92.8 (55.6–99.6) to 80.6 (32.0–93.1) GSU, corresponding to an improvement in the clinical status of patients.